2021
DOI: 10.1084/jem.20202033
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mechanosensitive MDM4 promotes lung fibrosis resolution in aged mice

Abstract: Aging is a strong risk factor and an independent prognostic factor for progressive human idiopathic pulmonary fibrosis (IPF). Aged mice develop nonresolving pulmonary fibrosis following lung injury. In this study, we found that mouse double minute 4 homolog (MDM4) is highly expressed in the fibrotic lesions of human IPF and experimental pulmonary fibrosis in aged mice. We identified MDM4 as a matrix stiffness–regulated endogenous inhibitor of p53. Reducing matrix stiffness down-regulates MDM4 expression, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 145 publications
(164 reference statements)
3
42
0
Order By: Relevance
“…MDM4 is highly expressed in the fibrotic lesions of human IPF and experimental pulmonary fibrosis in aged mice. Our studies provides evidence that mechanosensitive MDM4 is a molecular target with promising therapeutic potential against persistent lung fibrosis associated with aging (Qu et al, 2021). Moreover, ECM stiffness is sensitive to exogenous TGF-β stimulation through inhibiting the interaction of inner nuclear membrane protein LEM domain-containing protein 3 (LEMD3) and SMAD2/3.…”
Section: Matrix Stiffness and Scaffoldingmentioning
confidence: 80%
“…MDM4 is highly expressed in the fibrotic lesions of human IPF and experimental pulmonary fibrosis in aged mice. Our studies provides evidence that mechanosensitive MDM4 is a molecular target with promising therapeutic potential against persistent lung fibrosis associated with aging (Qu et al, 2021). Moreover, ECM stiffness is sensitive to exogenous TGF-β stimulation through inhibiting the interaction of inner nuclear membrane protein LEM domain-containing protein 3 (LEMD3) and SMAD2/3.…”
Section: Matrix Stiffness and Scaffoldingmentioning
confidence: 80%
“…While remarkable efforts have been dedicated to elucidating the origin of myofibroblasts in self-resolving mouse models of lung fibrosis, such as the bleomycin model in young mice ( 12 ), studies investigating myofibroblast persistence in progressive models of lung fibrosis are limited. Prior studies have identified NADPH oxidase 4 (NOX4), mouse double minute 4 homolog (MDM4), and the transcription factor myogenic differentiation 1 (MyoD) as factors that contributed to myofibroblast senescence and apoptosis resistance during persistent lung fibrosis in aged mice ( 11 , 13 15 ). Consistent with these findings, we have recently shown that, similarly to IPF, activated fibroblasts accumulated and persisted in the fibrotic lungs of aged mice ( 16 , 17 ), further suggesting that increased myofibroblast survival and/or dysfunctional apoptosis in aging may be responsible for the abnormal myofibroblast accumulation and for the sustained lung fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 62 , 63 Moreover, recent preclinical data showed that lung injury can cause non-resolving pulmonary fibrosis through mechanical impairment of lung microenvironment thus suggesting a therapeutic window of opportunity in early SSc-ILD. 64 …”
Section: Discussionmentioning
confidence: 99%